Baby bumps and abortion drop: unpacking fertility trends during COVID-19 in Germany - Bujard, Martin; Huebener, Mathias (Discussion paper series, 2024)
Although abortion trends can be highly informative for understanding fertility reactions amid COVID-19 pandemic, this perspective is rarely taken yet. In contrast to many other countries, Germany has reached above-average fertility rates in the first years of the pandemic. However, in-depth subgroup analyses of these trends are lacking. This paper aims at an in-depth investigation of changes in births and abortions in Germany from the start of the COVID-19 pandemic up to the end of 2021, with a specific focus on the context of public containment measures over time and relevant subgroups. Using augmented interrupted time series models, we analyze official birth and abortion statistics across different socio-demographic groups and regions. We first document two significant "baby bumps", the first arising from conceptions after the first lockdown, the second during the second lockdown. Abortions remained at similar levels during the first year of the pandemic but declined significantly in later periods during the first three quarters of 2021 when the healthcare system was under strain. The magnitude of the drop in abortions corresponds to 43% of the increase in births of the second baby bump. Subgroup analyses show that our findings apply to various socio-demographic groups and are most pronounced among individuals aged 25 to 39 years. The fertility patterns contrast with trends in many high-income countries. We argue that Germany's robust social policies were likely to have stabilized total fertility rates during the crisis; however, the drop in abortions could also have contributed to this. Our study draws a nuanced picture of how the COVID-19 health crisis affected reproductive health outcomes. Analyses of fertility patterns during crises should pay attention to changes in abortions.
Keywords: Graue Literatur